Penggunaan Kiasan dan Makna dalam Lagu “Amin Paling Serius” Karya Sal Priadi dan Nadin Amizah - Shenandoah Dea Anisa; Virsa Nandita Puspa (Pusat Riset dan Inovasi Nasional, 2023)
This article discusses and examines the allusions and meanings in the lyrics of the song entitled 'Amin Paling Serius' by Sal Priadi and Nadin Amizah from the perspective of the use of language styles and allusions. Due to the development of pop music in Indonesia, Millennial and Z generation, children are more likely to like pop and foreign language songs so songs in Indonesian begin to fade and reduce listeners, therefore it is necessary to introduce Indonesian songs so that Millennial children are more familiar with their own culture. The method used in the research is descriptive qualitative. Based on the results of observations, the song 'Amin Paling Serius' uses five language styles and figures of speech, namely Smile, Metaphor, Personification, Antonomasia, and Hypocrisy in it. This song is also packaged poetically with symbolic words and means a journey of love with very romantic love and hope for lovers who strengthen each other, pray for each other and pray for each other to continue to a more serious level.